Can sensation of cold hands predict Raynaud's phenomenon or paraesthesia?. (10th May 2018) - Carlsson, D; Wahlström, J; Burström, L; Hagberg, M; Lundström, R; Pettersson, H; Nilsson, T
Abstract: Background: Raynaud's phenomenon and neurosensory symptoms are common after hand-arm vibration exposure. Knowledge of early signs of vibration injuries is needed. Aims: To investigate the risk of developing Raynaud's phenomenon and paraesthesia in relation to sensation of cold hands in a cohort of male employees at an engineering plant. Methods: We followed a cohort of male manual and office workers at an engineering plant in Sweden for 21 years. At baseline (1987 and 1992) and each follow-up (1992, 1997, 2002, 2008), we assessed sensation of cold, Raynaud's phenomenon and paraesthesia in the hands using questionnaires and measured vibration exposure. We calculated risk estimates with univariate and multiple logistic regression analyses and adjusted for vibration exposure and tobacco usage. Results: There were 241 study participants. During the study period, 21 individuals developed Raynaud's phenomenon and 43 developed paraesthesia. When adjusting the risk of developing Raynaud's phenomenon for vibration exposure and tobacco use, the odds ratios were between 6.0 and 6.3 (95% CI 2.2–17.0). We observed no increased risk for paraesthesia in relation to a sensation of cold hands. Conclusions: A sensation of cold hands was a risk factor for Raynaud's phenomenon. At the individual level, reporting a sensation of cold hands did not appear to be useful information to predict future development of Raynaud's phenomenon given a weak to moderate predictive value. For paraesthesia, the sensation of cold was not a risk factor and there was no predictive value at the individual level.